Reasons for presenteeism in nurses working in geriatric settings: a qualitative study - Fiorini, Luke Anthony; Griffiths, Amanda; Houdmont, Jonathan (Sciedu Press, 2018)
Objective: To explore the perceived causes of presenteeism in nurses on geriatric wards. Background: Presenteeism, defined as working when unwell, is associated with lost productivity and increased absenteeism. It is more commonly reported by employees in the healthcare sector than other sectors. Methods: An exploratory, qualitative study using semi- structured interviews, thematically analysed. Data collected via 18 recorded interviews with nurses working with patients on geriatric medical wards in Malta. Results: Four major themes emerged that related to nurses’ decisions to engage in presenteeism: illness perceptions, which included participants’ views and experiences of their own health complaints; attitudes to their employing organisation, co-workers and patients; organisational aspects such as culture and administrative arrangements; and personal reasons including illness behaviour preference and personal circumstances. Conclusions: Nurses’ decisions to attend work when unwell were reported as dependent upon four themes. Further studies are warranted to determine if findings are applicable to nurse populations other than those represented in this study. Implications: Workplace health promotion initiatives should target nurses’ management of their own health, particularly if they have chronic illnesses. Workplace policies and arrangements should be examined with a view to controlling presenteeism.